The Dynamics of Bacterial Communities During Traditional Nata de Coco Fermentation - CECILIA ANNA SEUMAHU; ANTONIUS SUWANTO; DEBORA HADISUSANTO; MAGGY THENAWIJAYA SUHARTONO (Microbiology Indonesia, 2007)
One of the important problems in traditional Nata de Coco (Nata) fermentation is production inconsistency due to strain or genetic variability reflecting mixed microbial communities involved in this process. This research was aimed at examine the population dynamics of the bacterial community during the fermentation processes. Samples were collected daily for six days from fermentation media derived from “good” and “bad” Nata fermentation. We compared the levels of bacterial diversity through amplified 16S-rRNA (ARDRA). DNA was extracted directly from the fermentation media and 16S-rRNA gene was amplified employing Universal Bacterial Primers. The amplicons were cloned into pGEM-T Easy vector, and restriction enzymes HaeIII and RsaI were used to generate ARDRA profiles. ARDRA phylotypes of DNA extracted from the fermentation medium obtained from different Nata qualities were compared. Phylotype profiles demonstrated unique bacterial community profiles for different conditions of Nata quality, which could be developed as a parameter to monitor Nata quality during fermentation. In this research we found that the dynamics of the bacterial population involved in Nata fermentation were a crucial factor for determining traditional Nata quality.